2014
DOI: 10.1007/s00426-014-0630-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring relations between task conflict and informational conflict in the Stroop task

Abstract: In this study, we tested the proposal that the Stroop task involves two conflicts--task conflict and informational conflict. Task conflict was defined as the latency difference between color words and non-letter neutrals, and manipulated by varying the proportion of color words versus non-letter neutrals. Informational conflict was defined as the latency difference between incongruent and congruent trials and manipulated by varying the congruent-to-incongruent trial ratio. We replicated previous findings showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 42 publications
5
34
0
1
Order By: Relevance
“…Understanding the extent to which top-down control mechanisms affect different conflicts contributes to our understanding of the flexibility of cognitive control mechanisms. Findings in the literature regarding the color-word Stroop task suggested similar adjustment of control modulation for informational and task conflict (e.g., Entel et al, 2015; Goldfarb & Henik, 2007; Kalanthroff & Henik, 2014). In contrast, the current study demonstrated an asymmetry between the informational and task conflicts.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Understanding the extent to which top-down control mechanisms affect different conflicts contributes to our understanding of the flexibility of cognitive control mechanisms. Findings in the literature regarding the color-word Stroop task suggested similar adjustment of control modulation for informational and task conflict (e.g., Entel et al, 2015; Goldfarb & Henik, 2007; Kalanthroff & Henik, 2014). In contrast, the current study demonstrated an asymmetry between the informational and task conflicts.…”
Section: Discussionmentioning
confidence: 83%
“…Most studies examined top-down mechanisms by examining the ability to inhibit reading of a single colored word, or examining several stimuli in which there was only one conflict that stemmed from the combination of all stimuli (i.e., Appelbaum et al, 2014; Bugg et al, 2011; Cohen et al, 1990; Entel et al, 2015; Gratton et al, 1992; Hutchison, 2011; Kalanthroff et al, 2015; Lindsay & Jacoby, 1994; Logan & Zbrodoff, 1979; Steinhauser & Hubner, 2009; Tzelgov, Henik et al, 1992). In our study, we used the numerical Stroop task in which participants were asked to compare the magnitude of numbers or their physical sizes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations